Raoultella terrigena and Pectobacterium carotovorum in vegetables in two provinces of Costa Rica - Cubero-Agüero, Diego (2021)
Introduction. Soft rot in crops is caused by a group of bacteria capable of secreting enzymes that degrade pectin in the cell wall of the plants and causes significant economic losses in agriculture worldwide. In Costa Rica, there is few data available about the distribution, hosts, and genetic diversity of the causal agents of disease. Objective. To identify the presence of bacteria causing soft rot in vegetables located in Cartago and Alajuela using molecular and enzymatic analysis, and pathogenicity techniques. Materials and methods. The study was carried out between July and October 2017 in Cartago and Alajuela, Costa Rica. Plants with soft roth symptoms were collected: sweet chili (Capcicum annum), onion leaves and bulbs (Allium cepa), zucchini plants (Cucurbita pepo), tomato fruits (Solanum lycopersicum), and potato plants (Solanum tuberosum). Bacterial isolation was performed on a selective violet crystal and pectate (CVP) medium. Hypersensitive reaction (RH) tests were performed, the isolates were inoculated into sweet chili leaves and pathogenicity tests (Koch´s postulates) were carried out for the positive bacteria. The isolates were identified by the 16S RNA-Ribosomal gene. Results. Five bacteria with pectinolytic activity were isolated: Pt1-A, 6-M2, Ech2A, CfspA, and Cfsab. According to the pathogenicity analysis, CfspA, Cfsab, and Ech2A strains were causal agents of soft rot in chile. It was not possible to reproduce the symptoms in onion and potato. According to the molecular identification, CfspA and Cfsab strains were classified within the Pectobacterium carotovorum clade, while Ech2A was classified as Raoultella terrigena. Conclusion. Raoultella and Pectobacterium carotovorum were considered the causal agents of soft rotting of chili in the areas of Cartago and Alajuela respectively.